Social Unrest of Betawi‘s Traditional Arts and Culture Performers during COVID-19 Pandemic - Iwan Henry Wardhana; Renny Nurhasana (The Winners, 2020)
The COVID-19 pandemic quarantine had caused social unrest in many sectors of society due to sudden downturn of economic activities as well as severe decrease of income. The research aimed to reduce social unrest among Betawi’s traditional arts and culture performers, prevent unrest from rising to a greater level and preserve Betawi’s traditional arts and culture in Jakarta. The social unrest data were collected by Jakarta Capital City Government, through Jakarta Culture Office via an intensive interview with Betawi’s traditional arts and culture figures. The results of the interviews were identified and used as the basis for formulating policies that could reduce social unrest in the Betawi arts and cultural performers. The results show that Betawi’s traditional art and culture performers' unrest can be overcome and preventedfrom escalating to the next level.